Caffeic Acid Inhibits UVB‐induced Inflammation and Photocarcinogenesis Through Activation of Peroxisome Proliferator‐activated Receptor‐γ in Mouse Skin. (13th October 2015) - Balupillai, Agilan; Prasad, Rajendra N.; Ramasamy, Karthikeyan; Muthusamy, Ganesan; Shanmugham, Mohana; Govindasamy, Kanimozhi; Gunaseelan, Srithar
Abstract: In this study, the effect of caffeic acid (CA) on both acute and chronic UVB‐irradiation–induced inflammation and photocarcinogenesis was investigated in Swiss albino mice. Animals were exposed to 180 mJ cm −2 of UVB once daily for 10 consecutive days and thrice weekly for 30 weeks for acute and chronic study respectively. UVB exposure for 10 consecutive days showed edema formation, increased lipid peroxidation and decreased antioxidant status with activation of inflammatory molecules such as TNF‐ α, IL‐6, COX‐2 and NF‐ κ B. However, CA (15 mg per kg.b.wt.) administration before each UVB exposure decreased lipid peroxidation, inflammatory markers expression and enhanced antioxidant status probably through the activation of peroxisome proliferator‐activated receptors (PPAR γ ) in the mice skin. PPAR γ is considered a potential target for photochemoprevention because it inhibits UVB‐mediated inflammatory responses. In this study, UVB exposure for 30 weeks caused squamous cell carcinoma and upregulation of iNOS, VEGF and TGF‐ β and downregulation of p53 and tumor incidence in the mice skin. Both topical (CAT) and intraperitoneal (CAIP) treatment before each UVB exposure downregulates iNOS, VEGF, TGF‐ β, upregulates p53 and reduces tumors multiplicity in the mice skin. Thus, CA offers protection against UVB‐induced photocarcinogenesis probably through activation of anti‐inflammatory transcription factor PPAR γ in the mice. Abstract : Excessive UVB irradiation increased the skin tumor incidence, oxidative imbalance, angiogenic and inflammatory signaling and activation of NF‐ κ B, a transcription factor involved in inflammation in mouse skin. Caffeic acid administration before each UVB irradiation decreased the angiogenic and inflammatory signaling with decreased expression of NF‐kB. Caffeic acid might act as agonist of PPAR γ, a transcription factor involved in the anti‐inflammation reaction, and inhibit NF‐ κ B‐mediated inflammatory reactions thereby inhibiting photocarcinogenesis in mouse skin.